2012
DOI: 10.1890/11-1083.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicted eelgrass response to sea level rise and its availability to foraging Black Brant in Pacific coast estuaries

Abstract: Managers need to predict how animals will respond to habitat redistributions caused by climate change. Our objective was to model the effects of sea level rise on total eelgrass (Zostera marina) habitat area and on the amount of that area that is accessible to Brant geese (Branta bernicla), specialist grazers of eelgrass. Digital elevation models were developed for seven estuaries from Alaska, Washington, California (USA), and Mexico. Scenarios of future total eelgrass area were derived from combinations of es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…With the prediction that extreme events will become more frequent and that average MSL will increase, we are concerned that eelgrass will not have the ability to shift its distribution upward or downward rapidly enough to survive, and that eelgrass may be eliminated especially in tidal flat-dominated systems such as Willapa Bay. Modeling by Shaughnessy et al (2012) showed that eelgrass should expand considerably (i.e. Recent data also indicate that the tidal amplitude is increasing in the eastern Pacific Ocean, which complicates assessment of sealevel effect on eelgrass growth and distribution (Jay, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…With the prediction that extreme events will become more frequent and that average MSL will increase, we are concerned that eelgrass will not have the ability to shift its distribution upward or downward rapidly enough to survive, and that eelgrass may be eliminated especially in tidal flat-dominated systems such as Willapa Bay. Modeling by Shaughnessy et al (2012) showed that eelgrass should expand considerably (i.e. Recent data also indicate that the tidal amplitude is increasing in the eastern Pacific Ocean, which complicates assessment of sealevel effect on eelgrass growth and distribution (Jay, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, some key recent modelling studies based on Zostera spp. in North America (Kairis & Rybczyk, ; Carr et al ., ; Shaughnessy et al ., ) have found the effects of SLR on seagrass to be variable and context dependent: both predicted increases or decreases in extent of seagrass have been reported (Kairis & Rybczyk, ; Shaughnessy et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of the decline in annual survival of adults can be attributed to increased harvest rate, which has increased 2−4‐fold since 2000 (Sedinger et al , Leach et al ). Increased retrieved harvest can only account for about 48% of the decline in annual survival of adults (Leach et al ), however, suggesting other factors like quality of migration or winter habitats are also playing a role (Ward et al , Shaughnessy et al ).…”
mentioning
confidence: 99%